The Medical‐Legal Responsibilities of a Dialysis Unit Medical Director. Issue 5 (12th December 2013) - Vaqar, Sarosh; Murray, Brian; Panesar, Mandip
Abstract The specialty of Nephrology, by virtue of its relationship with the dialysis procedure, is highly vulnerable to litigation. As is the case with all nephrologists, a dialysis unit medical director is not immune to medical malpractice suits, and can be held liable for any act of perceived or potential harm to any dialysis patient, regardless of the director's level of involvement. The medical director, per the Centers for Medicare and Medicaid Services (CMS) Conditions of Participation, accepts the responsibilities, accountability, and consequent legal liabilities of the quality of the medical care provided to every dialysis patient in the unit. This review is a synopsis of lawsuits filed against medical directors of dialysis units in the past forty years. Six categories of legal actions were noted; medical malpractice, fraudulent claims, self‐referral and Stark Law, discrimination, negligence, and violation of patient autonomy and dignity.